Nicotine exposure during lactation causes disruption of hedonic eating behavior and alters dopaminergic system in adult female rats. (1st May 2021) - Peixoto, T.C.; Moura, E.G.; Soares, P.N.; Rodrigues, V.S.T.; Claudio-Neto, S.; Oliveira, E.; Manhães, A.C.; Lisboa, P.C.
Abstract: Tobacco smoke during gestation is associated with increased consumption of palatable foods by the offspring in humans and rats. Postpartum relapse is observed in lactating women who quit smoking during pregnancy, putting their children at risk of adverse health outcomes caused by secondhand smoke. Nicotine is transferred through milk and alters the dopaminergic reward system of adult male rats, reducing dopamine action in the nucleus accumbens (NAc) and hypothalamic arcuate nucleus. Here, we evaluated the long-term effects of nicotine-only exposure during lactation on eating behavior, anxiety, locomotion, dopaminergic system, hypothalamic leptin signaling and nicotinic receptor in the adult female rat progeny. Two days after birth (PN2), Wistar rat dams were separated into control and nicotine (Nic) groups for implantation of osmotic minipumps that released respectively saline or 6 mg/kg nicotine. Lactating dams were kept with 6 pups. After weaning (PN21; nicotine withdrawal), only the female offspring were studied. Euthanasia occurred at PN180. Nic females showed hyperphagia, preference for a high-sucrose diet, increased anxiety-like behavior, lower tyrosine hydroxylase (TH), lower dopamine transporter and higher dopamine receptor (Drd2) in NAc; lower Drd1 in prefrontal cortex and lower TH in dorsal striatum (DS). These animals showed changes that can explain their hyperphagia, such as: lower leptin signaling pathway (Lepr b, pJAK2, pSTAT3) and Chrna7 expression in hypothalamus. Neonatal nicotine exposure affects the brain reward system of the female progeny differently from males, mainly decreasing dopamine production in NAc and DS. Therefore, Nic females are more susceptible to develop food addiction and obesity. Graphical abstract: Image 1